Visual function assessment of diagnostic radiography students. Issue 2 (May 2020) - Lockwood, P.; Blackman, A.
Abstract: Introduction: Deterioration of visual acuity (VA) and visual impairment has been linked to age-related subtle changes, gender, and a correlation to socioeconomic status. This study aimed to assess first-year diagnostic radiography students' visual functional abilities by applying the International Classification of Impairments, Disabilities and Handicaps (ICIDH) recommendations of functional VA screening and health-related quality of life questionnaire (HRQOL). Methods: The design followed the World Health Organisation (WHO) electronic VA testing of monocular sight using LogMAR charts and binocular vision using Snellen charts, and an HRQOL questionnaire assessing for reduced ability of visual-based tasks in activities of daily living (ADL). The data was evaluated in correlation to the participant's visual correction, age, gender, and socioeconomic background. Results: Seventy students were recruited, all meeting the WHO standard level for visual ability, with 100% ( n = 70/70) met or achieved above normal binocular vision, correlating to expected normal population results from published studies for age. The monocular vision demonstrated 74% ( n = 52/70) for the right eye, and 80% ( n = 56/70) for the left eye for normal vision levels. The results did not differ significantly between each eye ( p = 0.21), gender variations between the left eye ( p = 0.27) and the right eye ( p = 0.10) results were affected by sample ratio of females (80%; n = 56/70) to males (20%; n = 14/70), the visual correction did not impair binocular VA. The HRQOL assessment indicated no significant functional VA issues in the study sample. The study demonstrated no association between the participant's socioeconomic background that may influence their VA ability. Conclusion: The results provided normative binocular and monocular data on visual function in a sample of student radiographers and indicated that their thresholds align to normal (or near-normal) VA standards. Implications for practice: The visual health data was reviewed for subgroup comparison and trend analysis, and did not identify risk factors within this sample group that their VA and visual functioning would impact upon radiography clinical placement tasks and activities. The sample is not generalisable to the wider population; further studies are recommended.